Kesehatan Mental Perempuan dan Sinergitas Kebijakan Kesehatan Mental di Indonesia Terhadap Norma Internasional - Pratiwi, Tiffany Setyo (Jurnal Ilmiah Hubungan Internasional, 2024)
Indonesia is experiencing a mental health emergency. Mental health has long been an international norm thatratified by countries, including Indonesia. Global data and cases in Indonesia show that women suffer from more mental disorders than men. The causes of mental health disorders experienced by women come from biological factors due to hormonal changes, psychological reasons, social relationship, and the impact of environmental damage. So it is time for women's mental health to be given serious attention. Unfortunately, in this research found that Indonesia does not yet have specific regulations regarding mental health for women, only general rules that are implicitly stated in Law Number 17 of 2023 Article 76 that “everyone has the right to access mental health services that are safe, quality and affordable” also psychiatric research regarding mental disorders in Indonesia is still limited. Second, this research found that the contents of Article 76 do not match the reality on the ground which is still far from the goals. Third, the role of actors from femocrats, women's activists, and academics have built collaborative relationships through the formation of a cross-sector coordination forum, namely the Community Mental Health Steering Team (TPKJM) from the provincial, district/city and sub-districtlevels. Keywords: Women's Mental Health Indonesia; National Policy; International Norms; Velvet Triangles Concept,TPKJM.